To convergence and beyond? Human capital, economic adjustment and a return to growth - John FitzGerald (The Economic and Social Research Institute (ESRI), 2012)
This paper considers the impact on growth and convergence in the EU over the last 20 years of investment in human capital. It examines the current adjustment of a range of economies to the external imbalances at the beginning of the current crisis. Finally it considers how the adjustments under way will contribute to a return to long-term growth.
Keywords: 330